NEW DATA ON THE AGE AND TECTONIC POSITION OF THE PALEOZOIC DEPOSITS OF THE KHAN TENGRI MASSIF - Khristov Ye.V. (My University, 1989)
Existing theories on the geologic structure of Khan Tengri, a massif that is extremely difficult to reach and has the largest glaciers (North and South Inyl'chek) and highest peaks in the Tien Shan, are based on data obtained in the middle of the 1930's. In recent reviews on the geology of the area, it was shown that carbonate rocks and shales of Late Silurian-Early Devonian age are exposed on the upper reaches of the Inyl'chek River. The Khan Tengri massif has a nappe structure the main component of its northern part being a large antiform that extends along sides of the North and the South Inyl'chek Glaciers. The core of this antiform exposes a sequence as thick as 1000 m, composed of rhythmically alternating, dark polymict sandstones with graded bedding and black calcareous siltstones and mudstones.
Keywords: Paleozoic; Paleozoic; Палеозой